Five centuries resisting: The March of October 12 in Buenos Aires and Santiago de Chile as collective chronotopic memory and Amerindian revindication in Abya Yala - Mardones Charlone, Pablo; Fernández Droguett, Francisca (Instituto de Estudios Internacionales, 2017)
According to the chronicles of history, October 12th, 1492 is the day when Christopher Columbus arrived to the Caribbean. How then did this date become a day for reflection, protest and demand through an annual march that in 2016 completed 25 years without interruption in two of the largest cities in South America, Buenos Aires and Santiago? In both cities, which has historically been imagined as “white”, indigenous communities (both domestic and foreign) are the organizers of the march, which is driven by the festive contributions of indigenous musicians and dancers. In a place so far from the Caribbean, the date of the 500th anniversary of Columbus’ arrival has allowed for the crystallization of indigenous demands and generated a common sense of belonging withthe rest of the region. In this paper, we describe the context, genesis and history of the march and provide an analysis of the political uses of memory through a chronotropic reading (where a significant event from the past acquires relevance in the present and becomes significant in the future) in order to propose several strands of interpretation for the march’s emergence and its repercussions.